(untitled) (Fiep Bulletin - online, 2014)
The functional dependence so noticed on elderly stage is physiologically associated mainly to the physical qualities, such as strength, flexibility, aerobic and anaerobic resistance, localized resistance muscle, velocity, coordination, balance, rhythm, agility, and muscle relaxation (SOUSAet al, 2012). On the other hand, the morphological aspects are associated with increased muscle mass, reduction of adipose tissue, improvement and maintenance of bone mineral density, important to support of body posture. According to Filho (2006), Teixeira (2005), Balsamo and Simões (2005), and Mcadleet al. (2008), the regular physical activity has a goal of maintenance or revere the loss of these capacities so important in the life of any person. The aim of this review study is research the influences of the resistance training (RT)in the posture problems which contributes to the loss in a quality life of elderly people. The conclusion is that the regular systematic physical activity, as RT, prevents a severe loss and regains the morphological and physiological functional capacities caused by advanced age and sedentary, besides contribution to maintenance of balance and body posture which are so important to the reduction falls and a healthy aging.